The Impact of Internet Usage in the COVID-19 Pandemic Era: A Literature Review - Kusuma, Surya Puji; Yumni, Fathiya Lutfil; Uliyah, Musrifatul; Mukarromah, Nur (Indonesian Academia Health Sciences Journal, 2022)
Background: The internet is a network that can provide information or a virtual media that has various functions. Continuous internet use has an impact on physical health including eating disorders and sleep disorders, weight gain or loss, eye disorders such as dry eyes and blurred eyes, back pain, carpal tunnel syndrome, repetitive muscle injuries and chronic fatigue. Objectives: Identify the impact of internet use in the covid-19 pandemic era, Provide conclusions about the impact of internet use in the covid-19 pandemic era. Method : Literature Review of the impact of internet use in the era of the covid-19 pandemic. Search articles via the internet with database data: PNRI, PUBMED, ProQuest, EBSCO and Google Scholar. The review carried out 11 articles on the impact of internet use in the era of the covid-19 pandemic. Starting in 2019-2021. Results: Research conducted in eleven journals that researchers reviewed showed that the impact of internet use in the era of the COVID-19 pandemic showed positive and negative impacts. The journal that shows a positive impact is the use of the Internet to increase the reading interest of PLS ​​students. At IKIP Siliwangi, the journal is to increase students' reading literacy which makes students interested in reading. What shows a negative impact is the Potential for Internet Use Addiction to Indonesian Teenagers in the Early Period of the Covid-19 Pandemic and the Relationship between Intensity of Internet Use and Sleep Quality in Journal Students, namely internet addiction leading to internet addiction, sleep pattern disorders. Conclusion The current era of the COVID-19 pandemic has an impact on all aspects, including education. So that all students must be SFH. The impact of this condition causes excessive internet use, such as the results of research in the eleven journals. There are positive and negative impacts of using the internet. Therefore, as parents and the wider community, it is necessary to assist children in using the internet during the SFH period